Promote the Dissemination of the Poetry of the Tang Dynasty among Young Audiences through Visual Transformation Design - Luo, Chen; Chaetnalao, Atithep (Journal of Fine and Applied Arts Khon Kaen University, 2024)
Tang poetry stands as a precious cultural heritage of the Chinese poetry articulation. However, in the era of visual communication, it has encountered difficulties in communication to the young people. Therefore, this study conducted visual translational research on Tang poetry to (1) understand the contemporary young audiences’ reception of Tang poetry, (2) deduce design methods for its visual transformation, and (3) demonstrate the effectiveness of these methods in its dissemination. The research employed a mixed methodology comprising questionnaires, workshops, and exhibitions. The results show that the fundamental factor affecting the communication efficiency of Tang poetry is that the communication form of Tang poetry is obselete and lacking. Therefore, researchers will improve the effectiveness of the communication of Tang poetry by studying the visual transformation of Tang poetry.